MODELING OF LIVER FIBROSIS IN SMALL LABORATORY ANIMALS - Feruza Kh. Inoyatova; Maksud S. Khayitov; Rajab I. Isroilov (Central Asian Journal of Medicine, 2022)
Chronic toxic liver damage resulting in cirrhosis was caused by intraperitoneal administration of a 30% solution of CCl 4 in olive oil at a dose of 1 ml/kg of body weight 2 times a week for 30 days, followed by the introduction of a 50% solution in olive oil at a rate of 1 ml/kg. kg into the abdominal cavity for up to 50 days. To potentiate the hepatotoxic effect of CCl4 , the animals received orally 5 ml of 5% ethanol solution once a day, starting from the 3rd day of the experiment. The duration of the experiment was 60 days. Histological studies of the liver of experimental animals were carried out on the 20th, 30th, 40th, 50th and 60th days from the start of the experiment. Modeling of chronic toxic hepatitis with the transition to cirrhosis by the introduction of carbon tetrachloride with ethyl alcohol from the 20th day was accompanied by the development of massive necrosis in the central, third functional zone of the liver lobules. In the subsequent periods of the experiment, the development of a diffuse inflammatory reaction in the form of lymphohistiocytic infiltration was noted, mainly along the portal tracts and around the central veins. On the 60th day, the formation of dense cell infiltration and bundles of connective tissue in the form of portal cirrhosis around the vascular triads and central veins was noted, which was confirmed by staining the collagen fibers with picrofuchsin red.